Evaluation of E-Learning in E-Courses at Yarmouk University in light of E-Learning Quality Standards from Students' Point of View - Nabeela Belal Adnan Fattoum; Yousef Ahmad Eyadat; Mohammad Fuad Al-hawamdeh (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: This study aims to evaluate e-learning in e-courses at Yarmouk University in light of e-learning quality standards from the students' point of view. Methods: The study adopted a descriptive survey method. The study sample consisted of (361) male and female students enrolled in electronic courses at Yarmouk University during the second semester of the academic year 2017/2018. The sample was chosen through a convenient method. A questionnaire was built, and its validity and reliability were verified. Results: The results of the study show the availability of e-Learning quality standards from the perspective of students. The results also show that there are statistically significant differences in the degree of availability of e-learning quality standards from the students' point of view due to academic year in favor of first and second academic years. The results also showed that there were statistically significant differences in the degree of availability of e-learning quality standards from the students' point of view due to the impact of estimation in favor of "pass" and "good" options. Conclusion: Based on the results, the study recommends using online courses for different specializations as well as general courses.